دساست التأث شٍ التثب طٍ لوض حٌ هي هستخلص بًاث الح اٌء (Artemisia herba alba-Asso) و بًاث الش حٍ (Lawsonia inermis) على شًاط بعض أ ىًاع البكت شٍ اٌ - صحراوي, سميرة (جامعة الوادي University of Eloued, 2016)
في بذث بُ هزا دبون بُ حث يً يب يذيط ب بُ في بيئخ بُ ي يىاسد بَبحيت وان سًبه تً في إثشاء هزا ان جًبل ديث أجشي بُ دساست عه بَبث ورنك بخذضيش يضيج ي يسخخهض هزي ان بُبحي في ,(Artemisia herba-alba( و بَبث انشيخ (Lawsonia inermis) انذ بُء الإيثب ىَل وانسيكهىهكسب ببنخ قُيع ع ذُ دسجت انذشاسة انعبديت ي بَديت وببلاسخخلاص ببسخخذاو جهبص سىكسهي ع ذُ دسجت دشاسة عبنيت ي بَديت أخشي, ثى دسسج انفعبنيت انخثبيطيت ن ضًيج هز ان سًخخهصبث ضذ ثلاثت أ ىَاع ي انبكخيشيب يىجبت انغشاو وسبنبت بخ سًت حشاكيض يخخهفت. دذدث الأقطبس انخثبيطيت ,Pseudomonads , Esherichia coli, Staphylocoque blanc : انغشاو وقىس جَ ان خُبئج نخذذيذ انخشكيض انفعبل ويقبس تَ انفعبنيت بي ان سًخخهصبث, فكب يضيج يسخخهض ان بُبحي ببلإيثب ىَل في دسجت انذشاسة بكبفت انخشاكيض, يقبس خَب Staphylocoque blanc 91 يهى( ببن سُبت نهبكخيشيب - انعبنيت قذ أظهش أفضم قطش حثبيطي يخشاوح بي ) 8 بببقي ان سًخخهصبث. اn our research, we have tried to discuss the value of our surrounding environment of plants resources and enrich this trend so we have done a study about Henna plant ( Lawsonia inermis) and wormwood plant (Artemisia Herba-alba). We have prepared the combination of these 2 plants extract using 2 ways: so asking them in a temperature and using Soxhlet extractor in a high temperature. Then, we have studied the effectiveness inhibitory of these combination against 3 types of gram-positive bacteria and gram-negative bacteria: Esherichia coli, Staphylocoque blanc, Pseudomonads, using 5 different concentrations. the inhibitory areas has been determined and the results was compared to determined the effective concentration and compare the compare the exacts. The combination of the extract of the 2 plants in ethanol in a high temperature showed the best inhibitory results between (8–19mm) with Staphylocoque blanc compared to the other extracts.
مذكرة ماستر تخصص كيمياء
Keywords: انبكخيشيب. ,)Artemisia herba-alba( بَبث انشيخ ,)Lawsonia Inermis( انخأثيش انخثبيطي, بَبث انذ بُء; inhibitory impact, Henna plant (Lawsonia Inermis), wormwood plant (Artemisia herba-alba), bacteria.